Effect of two-cycle heat treatment on mechanical properties of ductile iron - A. Abdullah; M.F. Idham; A. Jaafar; A.F. Zubair; Mazlan Mohamed (2013)
The aim of this study is to investigate the mechanical properties of ductile iron after treatment with two-cycle heat treatment processes which modified from austempering. The modified heat treatments have two stages holding temperature. Ductile iron was austenitized at 900˚C for an hour and followed by transferring the sample to other furnace which was set at different temperatures of i) 250 ˚C; ii) 300 ˚C; iii) 350 ˚C without quenching for 1.5 hours. Tensile (ASTM E8M), impact (ASTM-E23-1990) and Rockwell hardness tests were carried out to study the mechanical properties of the ductile iron. It was found that the sample which was heat treated using two-cycle heat treatment process at temperature of 250˚C contributed to better absorbing impact energy properties and hardness properties. Meanwhile, sample that heat treated at 350 ˚C has higher tensile strength.